Aquaporin 4 inhibition alleviates myocardial ischemia-reperfusion injury by restraining cardiomyocyte pyroptosis. Issue 1 (1st January 2021) - Jiang, Qiong; Dong, Xianfeng; Hu, Danqing; Chen, Lejun; Luo, Yukun
ABSTRACT: Myocardial injury caused by ischemia-reperfusion is the main pathological manifestation of coronary artery disease (CAD), which is characterized by high mortality and morbidity. Thus, there's an urgent need to develop efficacious strategies and elucidate the underlying mechanisms to prevent or alleviate myocardial ischemia-reperfusion injury to improve the clinical outcomes in patients. In this study, we took advantage of a typical myocardial cell line of mice (HL-1) and cultured with or without an aquaporin 4 inhibitor (TGN-20 denoted as AQP4i) under normal conditions (NC), ischemia (IS) and ischemia reperfusion (IR), respectively. The cytomorphology, ultrastructure, cell vitality and expression pattern of apoptotic proteins were verified with scanning electron microscope (SEM), immunofluorescence staining, flow cytometry, quantitative real-time PCR and western-blotting analysis, respectively. HL-1 under IS or IR condition revealed higher expression of Aquaporin 4 (Aqp4) compared to the NC group, whereas showed similarity in cytomorphology and ultrastructure. Aqp4 inhibition was sufficient to improve the apoptotic cells in HL-1 while showed minimal effects to the other cellular vitality. Furthermore, the expression pattern of apoptotic proteins and anti-apoptotic proteins together with proinflammatory factors in HL-1 was effectively rescued by Aqp4i treatment both at the mRNA level and protein level. Ischemia and ischemia reperfusion caused higher expression of Aqp4 and resultant increase of cardiomyocyte pyroptosis. Myocardial ischemia-reperfusion injury of HL-1 was effectively alleviated by Aqp4 and pyroptosis inhibition. Our findings provided new references for myocardial ischemia-reperfusion injury management via targeting Aqp4-mediated pyroptosis of cardiomyocyte.